Hubungan Pengetahuan dan Perilaku Keluarga Dengan Kejadian TB Paru di Puskesmas Purwasari - Isnaeni, Isnaeni; Sudrajat, Aji Ajat (Universitas Malahayati, 2025)
ABSTRACT Until now, Tuberculosis is still one of the significant public health challenges globally. Those who have tuberculosis can easily spread the disease to others nearby through droplets when talking, coughing, or sneezing. Pulmonary tuberculosis is an infectious condition caused by mycobacterium tuberculosis. This particular bacteria is an acid-fast aerobic bacillus that spreads through the air. In almost every case, pulmonary tuberculosis infection occurs through inhalation of relatively small germ particles. If not treated properly, each individual with pulmonary tuberculosis has the potential to infect between 10 to 15 people each year. Referring to the World Health Organization's Global Tuberculosis Report, Indonesia is the country with the most cases in the world after India and China. It is estimated that the number of cases reaches 824,000 new cases each year. The discovery of new cases in 2019 was 562,049 cases (67%) of the estimated cases. In 2020, the number of new cases of pulmonary TB decreased due to the Covid-19 pandemic, namely 384,025 cases (47%) of the estimated cases. This study aims to determine the relationship between the level of knowledge and family behavior with the incidence of pulmonary TB at the Purwasari Health Center in 2024. The type of research used is quantitative research and the design used is